Military strategy principles, practices, and historical perspectives - Collins, John M. 1921- (Potomac Books, Inc., 2002)
John M. Collins has distilled the wisdom of history's great military minds to tutor readers on the necessary intellectual skills to win not only battles but also wars. He illuminates practices that worked well or poorly in the past, together with reasons why. He discusses national security interests, strategic building blocks, military strategies across the conflict spectrum, methods for developing talent and strategic acumen, and recent case studies that put principles into practice. Collins never tells readers what to think, but in Military Strategy he provides them with the intellect